Dimensional accuracy and detail reproduction of two hydrophilic vinyl polysiloxane impression materials tested under different conditions - Preeti Agarwal Katyayan; Natarajan Kalavathy; Manish Katyayan (Wolters Kluwer Medknow Publications, 2011)
Background and Objectives: A limitation of vinyl polysiloxane (VPS) impression materials is hydrophobicity, and manufacturers have added surfactants and labeled these new products as "hydrophilic." The purpose of this investigation was to evaluate and compare the dimensional accuracy and surface detail reproduction of two hydrophilic VPS impression materials under dry, moist, and wet conditions. Materials and Methods: Ten impressions were made under dry, moist, and wet conditions respectively, with monophase, and regular body VPS impression material using a stainless steel metal die similar to that described in American Dental Association (ADA) specification 19, with lines scribed on it. Dimensional accuracy was measured by comparing the average length of the middle horizontal line in each impression to the same line on the metal die, by using a measuring microscope. The surface detail was evaluated. A one-way analysis of variance and Student t-test were used to compare mean dimensional changes (α = 0.05). Results: Conditions (dry, moist, and wet) did not cause significant adverse effects on the dimensional accuracy of either material. The mean dimensional changes were 0.00084% (+0.00041%) for monophase and 0.00119% (+0.00033%) for regular body. Monophase material was satisfactory in detail reproduction 100% of the time in dry conditions, 90% in moist, and only 20% in wet conditions. The regular body showed 100% satisfactory impressions in dry, 80% in moist, and 10% in wet conditions. With the additional smooth surface evaluation, only under dry conditions impressions with clinically acceptable surface quality were produced. Conclusions: Dimensional changes for both materials were well within ADA standards of minimal shrinkage value of 0.5%.